Understanding the role of social media on prospective local and international students’ selection of university - Tengku Elena Tengku Mahamad,; Melina Mahpuz,; Baby Anusha Nur Mohamed Thaheer,; Saraswati, Girindra Putri Dewi; Burhanudin, Muhamad; Setyadharma, Andryan (Penerbit Universiti Kebangsaan Malaysia, 2024)
Universities globally utilise social media platforms to disseminate information to prospective students. However there's a scarcity of research regarding the role of social media in promoting universities as international education hubs, especially in Asia. This study aims to investigate the impact of social media in promoting Asian universities, focusing on the preferences and behaviours of prospective undergraduate students from Malaysia and Indonesia. A qualitative research approach was employed, involving the recruitment of 12 undergraduate students from both countries. Data collection was conducted through online, in-depth, and semi-structured interviews. The majority of participants rely on social media platforms to gather information about potential universities and courses, citing ease of navigation and appeal compared to traditional websites and other platforms. However, universities demonstrate a lack of engagement with users, hindering the acquisition of comprehensive information about the institution. These findings offer valuable insights for universities to understand the information and social media elements that prospective students commonly seek on social media platforms. Additionally, they provide guidance on effective strategies for engaging with and recruiting students. Ultimately, this research may assist universities in better promoting themselves as international education institutions, particularly in the Asian context.